Lamb performance and estimation of starch digestibility of diets with different protein sources - Queiroz, Mário Adriano Ávila; Susin, Ivanete; Pires, Alexandre Vaz; Mendes, Clayton Quirino; Gentil, Renato Shinkai; Almeida, Omer Cavalcanti; Amaral, Rafael Camargo do; Mourão, Gerson Barreto (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the influence of protein sources on feedlot lambs performance, carcass and meat characteristics, and to estimate starch digestibility of high grain diets. Twenty-eight Santa Inês ram lambs were selected in a complete randomized block design, according to body weight and age in the beginning of the experiment. Protein sources were the following meals: soybean, peanut, canola, and cottonseed in isonitrogenous diets with 90% concentrate and 10% roughage (coast-cross hay). Four ram lambs (48 kg) were used to determine starch digestibility in a 4x4 latin square design, and starch digestibility was estimated by fecal concentration of starch. There were no differences (p > 0.05) for dry matter intake, average daily gain, feed conversion, carcass characteristics and meat quality, among the protein sources evaluated. Determination coefficient for starch digestibility was 93%. Fecal starch content is an accurate indicator of the starch digestibility estimation in lambs feeding high grain diets, independently of the protein source used.